A COMPARATIVE EFFECT OF WRITING WORKSHOP AND JOURNAL WRITING TECHNIQUES BASED ON TEXT TYPES ON THE EIGHTH GRADE STUDENTSâ WRITING COMPETENCY AT SMP NEGERI 1 SINGARAJA IN THE ACADEMIC YEAR 2012/2013 - Suprianti, Gusti Ayu Putu; Tantra, Dewa Komang; Padmadewi, Ni Nyoman (Jurnal Pendidikan Bahasa Inggris, 2013)
Â Abstract This study aimed at comparing the effect of different teaching techniques (Journal Writing and Writing Workshop Techniques) based on text types (recount and narrative texts) on studentsâ writing competency. Post-test Only Comparison Group Design was applied as the research design. After the treatment sessions, post-test was administered to discover the impact of the treatments. The data obtained from the post-test were analyzed by using descriptive and inferential statistical analyses. Through descriptive analysis, it was found that the mean scores of the group who was taught both narrative and recount text by using Journal Writing Technique was higher than the group who was taught by using Writing Workshop. In other words, the group who was taught by using Journal Writing Technique tends to perform better than group who was taught by using Writing Workshop Technique. The difference between writing competency of the students who were taught using different teaching techniques was analyzed through two-way Anova. Based on the result of the hypothesis testing, it was found that there was a significant difference between the two teaching techniques on studentsâ writing competency and there was no interactional effect between the two teaching techniques and the text types on studentsâ writing competency. Â Keywords: writing competency, journal writing, writing workshop, text types